[By the Honourable John Nanfan, Esq ; His] Majesties lieut. govern[our and commander in chief in and over the prov]ince of New-York ... [A pr]oclama[tion] ... : [Given at Fort William] Henry in New-York, this 2d. Day of March, 1701 . ([Printed by Willia]m Bradford, printer to the Kings Most Excellent [Majesty in] New-York, 1701)
Proroguing the General Assembly to the third Tuesday in April, 1701.